TNF inhibitors are produced spontaneously by rheumatoid and osteoarthritic synovial joint cell cultures: evidence of feedback control of TNF action. - Brennan, F; Gibbons, D; Cope, A; Katsikis, P; Maini, R; Feldmann, M (1995)
We have proposed the hypothesis that tumour necrosis factor alpha (TNF-alpha) has a pivotal role in the pathogenesis of rheumatoid arthritis, based on in vitro observations that in RA synovial joint cell cultures removal of TNF-alpha, inhibited other potentially pathogenic cytokines such as the equally proinflammatory cytokine interleukin 1 (IL-1) and the macrophage activating factor, GM-CSF. Here we describe that in both rheumatoid (RA) and osteoarthritic (OA) synovial cultures there is a homeostatic mechanism to regulate the activities of TNF-alpha. This concept is based on several observations. First in these synovial joint cell cultures the substantial discrepancy between the levels of bioactive and immunoreactive TNF-alpha indicates the presence of an inhibitor. Second, TNF binding proteins are produced spontaneously, which are the soluble variants of surface p75 and p55 TNF receptor. The amount of soluble TNF receptors (sTNF-R) produced varied between cultures; p75 sTNF-R was more abundant than p55 sTNF-R (as detected by ELISA), and both were produced at higher levels by RA synovial joint cells in culture, compared to OA cultures. These TNF binding proteins act as endogenous inhibitors of TNF-alpha, since blocking their activity in synovial joint cell culture supernatants with MoAb to p55 and p75 sTNF-R enhanced their cytotoxic activity in the TNF bioassay. The regulation of production of these sTNF-R in synovial joint cell cultures is important as the balance between TNF-alpha and sTNF-R production may determine the outcome of the inflammatory process.